2017
DOI: 10.1093/ehjqcco/qcx048
|View full text |Cite
|
Sign up to set email alerts
|

Low diagnostic yield of non-invasive testing in patients with suspected coronary artery disease: results from a large unselected hospital-based sample

Abstract: These data confirm the very low diagnostic yield of non-invasive and invasive assessment of CAD in current clinical practice, particularly in women and in patients with atypical symptoms. Data call for a more rational approach to avoid unnecessary testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Our study shows a low rate of MACE and mortality while disappearance of angina was observed in 51, 62%. Several studies have explored the prognostic impact of stable angina in patients with CAD [5,6,7,8,21,22]. In the Multinational CLARIFY Study, among 7212 (22.1%) patients who reported angina at baseline, angina disappeared (without coronary revascularization) in 39.6% at 1 year [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows a low rate of MACE and mortality while disappearance of angina was observed in 51, 62%. Several studies have explored the prognostic impact of stable angina in patients with CAD [5,6,7,8,21,22]. In the Multinational CLARIFY Study, among 7212 (22.1%) patients who reported angina at baseline, angina disappeared (without coronary revascularization) in 39.6% at 1 year [5].…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in Societies of Cardiology guidelines, management strategies include lifestyle modification, risk factor reduction, pharmacological, and invasive management if significant obstructive CAD is present [1]. Several studies have explored the prognostic impact of stable angina in patients with CAD [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Как уже отмечалось ранее, широкое использование неинвазивных тестов у больных с подозрением на ИБС привело к тому, что только 6-10% таких тестов на ишемию миокарда имели положительный результат [26]. Более точная оценка риска обструктивной ИБС с помощью определения клинической вероятности по одной из предложенных выше моделей, конечно, уменьшит число неинформативных неинвазивных тестов, однако проблема выбора оптимального неинвазивного теста сохраняется.…”
Section: алгоритм выбора неинвазивного/инвазивного обследованияunclassified
“…Широкое использование неинвазивных тестов у больных с подозрением на ИБС привело к неожиданному результату -только 6-10% НИТ на ишемию миокарда имели положительный результат [26], и в предыдущих рекомендациях при ПТВ менее 15% предлагалось не проводить дальнейшего обследования [5]. Дальнейшие исследования подчеркнули обоснованность использования отметки именно 15% как критерия непроведения дальнейших диагностических тестов.…”
Section: выбор неинвазивных и инвазивных диагностических тестовunclassified